2011
DOI: 10.1158/1078-0432.ccr-10-0250
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Soluble Form of B7-H1 That Retains Immunosuppressive Activity and Is Associated with Aggressive Renal Cell Carcinoma

Abstract: Purpose Release of inhibitory coregulatory proteins into the circulation may represent one mechanism by which tumors thwart immune responses. Our objective was to determine whether sB7-H1 levels in patients with clear cell renal cell carcinoma (ccRCC) are associated with pathologic features and patient outcome. Experimental Design We developed an ELISA for quantification of sB7-H1 in biologic fluids. Biochemical confirmation of the measured analyte as sB7-H1 was done by protein micro-sequencing using superna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
310
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 325 publications
(321 citation statements)
references
References 37 publications
7
310
2
2
Order By: Relevance
“…11,23 Serum levels of sPD-1 and sPD-L1 have been reported to be independent prognostic factors in different solid tumors susceptible to immunotherapy targeting the PD-1 axis. 13,14,24 Regulation, provenience and function of the soluble forms of PD-1 and PD-L1 in cancer are still under discussion. 24 This is the first study to examine serum levels of sPD-1 and sPD-L1 in advanced PC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,23 Serum levels of sPD-1 and sPD-L1 have been reported to be independent prognostic factors in different solid tumors susceptible to immunotherapy targeting the PD-1 axis. 13,14,24 Regulation, provenience and function of the soluble forms of PD-1 and PD-L1 in cancer are still under discussion. 24 This is the first study to examine serum levels of sPD-1 and sPD-L1 in advanced PC.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] High levels of soluble plasma PD-L1 (sPD-L1) were described as an adverse prognostic factor in several malignancies susceptible to PD-1/PD-L1 blockade, including renal cell cancer and hepatocellular carcinoma (HCC). 13,14 To date, provenience, regulation and immunologic function of sPD-1 and sPD-L1 in cancer remain uncertain. Plasma levels of sPD-1 and sPD- L1 have not yet been determined conjointly in any cancer type.…”
Section: Introductionmentioning
confidence: 99%
“…Frigola et al. reported that an elevated preoperative level of soluble PD‐L1 is associated with an increased risk of death from ccRCC, and they suggested that release of soluble PD‐L1 molecules may be a mechanism by which tumors impair systemic antitumor immunity, suggesting that inactivation or removal of soluble PD‐L1 from the serum could be clinically beneficia 26. Taken together, these findings have focused attention on blockade of PD‐1/PD‐L1 as a possible strategy for antitumor immunotherapy in patients with advanced RCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, as Frigola et al. suggested, systemic effects either by recirculation of immune cells through PD‐L1, B7‐H4, and VEGF‐positive tumor sites or by the release of biologically active soluble forms of PD‐L1, B7‐H4, and VEGF into the circulation cannot be excluded, indicating that both scenarios can contribute to global immunosuppression 26.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the virus integrated into an intron flanked by exons 4 and 5, and expression levels of exons 5-7 were attenuated, suggesting that viral integration into this locus resulted in an altered form of PDL1 that is expressed at high levels. Alternative PDL1 transcripts have been reported (37,38) and associated with poor prognosis in renal cell carcinoma (37).…”
Section: Hpv Integrations Are Associated With Somatic Alterations Of Keymentioning
confidence: 99%